Alantolactone Inhibits Melanoma Cell Culture Viability and Migration and Promotes Apoptosis by Inhibiting Wnt/β-Catenin Signaling - Zhang, Lingzhao; Chen, Jiayi; Chen, Yangmei; Zou, Daopei; Pu, Yihuan; Wei, Mengqi; Huang, Yanran; Li, Yuxin; Huang, Qing; Chen, Jin (Anti-cancer agents in medicinal chemistry, 2023)
Melanoma is a highly invasive and metastatic malignant tumor originating from melanocytes and is associated with a poor prognosis. Surgical resection and chemotherapy are currently the main therapeutic options for malignant melanoma; however, their efficacy is poor, highlighting the need for the development of new, safe, and effective drugs for the treatment of this cancer. To investigate the effects of alantolactone (ALT) on the proliferative, migratory, invasive, and apoptotic ability of malignant melanoma cells and explore its potential anticancer mechanism. Melanoma cells (A375 and B16) were treated with different concentrations (4, 6, 8, and 10 μmol/L) of ALT, with DMSO and no treatment serving as controls. The effects of the different concentrations of the drug on cell proliferation were assessed by crystal violet staining and CCK-8 assay. The effects on cell migration and invasion were detected by wound healing and Transwell assays, respectively. Flow cytometry was used to evaluate the effects of the drug on apoptosis and the cell cycle. ALT target genes in melanoma were screened using network pharmacology. Western blotting was used to measure the expression levels of the proliferation-related protein PCNA; the apoptosisrelated proteins Bax, Bcl-2, and caspase-3; the invasion and metastasis-related proteins MMP-2, MMP-7, MMP-9, vimentin, E-cadherin, and N-cadherin; and the canonical Wnt signaling pathway-related proteins β-catenin, c-Myc, and p-GSK3β. In addition, an l model of melanoma was established by the subcutaneous injection of A375 melanoma cells into nude mice, following which the effects of ALT treatment on malignant melanoma were determined in vivo. Compared with the controls, the proliferative, migratory, and invasive capacity of ALT-treated melanoma cells was significantly inhibited, whereas apoptosis was enhanced (P<0.01), showing effects that were exerted in a dose-dependent manner. The expression levels of the pro-apoptotic proteins Bax and caspase-3, as well as those of the interstitial marker E-cadherin, were upregulated in melanoma cells irrespective of the ALT concentration (P<0.05). In contrast, the expression levels of the anti-apoptotic protein Bcl-2, the proliferation-related protein PCNA, and the invasion and metastasis-related proteins MMP-2, MMP-7, MMP-9, N-cadherin, and vimentin were downregulated (P<0.05). The network pharmacology results indicated that GSK3β may be a key ALT target in melanoma. Meanwhile, western blotting assays showed that ALT treatment markedly suppressed the expression of β-catenin as well as that of its downstream effector c-Myc, and could also inhibit GSK3β phosphorylation. ALT can effectively inhibit the culture viability, migration, and invasion of A375 and B16 melanoma cells while also promoting their apoptosis. ALT may exert its anti-melanoma effects by inhibiting the Wnt/β-catenin signaling pathway. Combined, our data indicate that ALT has the potential as an effective and safe therapeutic drug for the treatment of melanoma.